Study of p40 is superior to p63 for the diagnosis of pulmonary squamous cell carcinoma on cytological smears - Rao, S. Nageshwar; Vutukuru, Anuradha; Durga, K.; Mithila, K. B.; V., Sailaja; Sreedhar, Vijay (International Journal Of Community Medicine And Public Health, 2024)
Background: Histology and genetically driven management are the current standard in carcinoma lung. Adequate tissue is a challenge in a few cases. While liquid biopsy is an, it’s an always preferred to get an initial cyto/histo morphological confirmation. While the immune-histo chemistry (IHC) is a proven method to differentiate the squamous vs adeno carcinoma, the role of various “immuno-cyto-chemical” makers were not studied widely. Methods: This is a retrospective (July 2018 to December 2018) for random sample collection and prospective (Jan 2019-August 2019) study conducted from in the Department of pathology, govt. chest hospital Osmania medical college, Hyderabad as a part of PG dissertation, 120 subjects with cytological diagnosis of non-small cell lung carcinoma were analyzed during this period and others were excluded. Results: Out of 120 cases 80-adenocarcinoma (ADC) and 40-squamous cell carcinoma (SCC). Most of the patients are in 61-70 years, 20 are 71-80 years, 20 between 51-60 and 10 are between 40-50 years. In this study sensitivity of p63 and p40 is equal, but specificity and positive predictive value are higher for p40 for diagnosis of SCC. Conclusions: Immuno-cyto-chemistry is still a valid option in selected cases where getting a biopsy is difficult. Our findings recommend the use of p40 immuno staining rather than p63 as a squamous cell marker.